Oxygen evolution reaction driven co-reactant-free antifouling electrochemiluminescence sensor based on electrocatalytic macromolecular heterocyclic compounds/electrically neutral hydrogel - Lei Tian; Luting Yan; Zekun Ren; Chao Wang; Xia Sun; Yemin Guo; Yanyan Zhang (Food Chemistry, 2025)

Self-calibrating ratiometric aptasensor for simultaneous detection of Cd(II) and Vibrio parahaemolyticus on a needle electrode platform - Qi Guo; Lei Tian; Luting Yan; Yuhao Zhang; Zekun Ren; Chao Wang; Xia Sun; Yemin Guo; Elena Zavyalova; Yanyan Zhang (Food Bioscience, 2025)

Coreactant-free electrochemiluminescent biosensor for detection of Staphylococcus aureus based on host–guest structure of Arg/ATT-AuNCs and DNA nanomachines - Luting Yan; Lei Tian; Yuhao Zhang; Qi Guo; Xia Sun; Yemin Guo; Falan Li; Qingqing Yang; Yanyan Zhang (Chemical Engineering Journal, 2025)

Electroluminescence aptasensor based on tetrahedral DNA nanostructure with exonuclease-assisted target cycling for detection of acetamiprid - Jingjing Liu; Lingjun Geng; Haifang Wang; Jingcheng Huang; Shuxian Zhou; Luting Yan; Lei Tian; Yaoting Mou; Pengwei Zhang; Junhao Zhao; Ziping Cai; Mingxin Zhao; et al. (Food Research International, 2024)

Atorvastatin Promotes Pro/anti-inflammatory Phenotypic Transformation of Microglia via Wnt/β-catenin Pathway in Hypoxic-Ischemic Neonatal Rats - Luting Yu; Lingyi Huang; Yuanyuan Zhao; Shixi Liu; Ruixi Zhou; Yan Yue; Hao Sun; Xiaojuan Su; Qian Liu; Shiping Li; Junjie Ying; Fengyan Zhao; et al. (Molecular Neurobiology, 2024)
Inflammatory reaction plays a key role in the pathogenesis of hypoxic-ischemic encephalopathy (HIE) in neonates. Microglia are resident innate immune cells in the central nervous system and are profoundly involved in neuroinflammation. Studies have revealed that atorvastatin exerts a neuroprotective effect by regulating neuroinflammation in adult animal models of brain stroke and traumatic brain injury, but its role regarding damage to the developing brain remains unclear. This study aimed to clarify the effect and mechanism of atorvastatin on the regulation of microglia function in neonatal hypoxic-ischemic brain damage (HIBD). The oxygen glucose deprivation (OGD) of microglia and neonatal rat HIBD model was established. Atorvastatin, recombinant sclerostin protein (SOST), and XAV939 (degradation of β-catenin) were administered to OGD microglia and HIBD rats. The pathological changes of brain tissue, cerebral infarction volume, learning and memory ability of rats, pro-inflammatory (CD16 + /Iba1 + ) and anti-inflammatory (CD206 + /Iba1 + ) microglia markers, inflammation-related indicators (Inos, Tnfα, Il6, Arg1, Tgfb, and Mrc1), and Wnt/β-catenin signaling molecules were examined. Atorvastatin reduced OGD-induced pro-inflammatory microglia and pro-inflammatory factors, while increasing anti-inflammatory microglia and anti-inflammatory factors. In vivo, atorvastatin attenuated hypoxia-ischemia (HI)-induced neuroinflammation and brain damage. Mechanistically, atorvastatin decreased SOST expression and activated the Wnt/β-catenin signaling pathway, and the administration of recombinant SOST protein or XAV939 inhibited Wnt/β-catenin signaling and attenuated the anti-inflammatory effect of atorvastatin. Atorvastatin promotes the pro/anti-inflammatory phenotypic transformation of microglia via the Wnt/β-catenin pathway in HI neonatal rats. Atorvastatin may be developed as a potent agent for the treatment of HIE in neonates.

Novel and legacy brominated flame retardants in snakes and frogs: Tissue distribution, biomagnification, and maternal transfer - Guanzhen Sun; Xinyu Du; Yan Wu; Ge Yin; Luting Chen; Xiaojun Liu; Yihui Zhou; Yanling Qiu; Tian Lin (Science of The Total Environment, 2023)